Pedophilia in The Novel Lolita by Vladimir Nabokov - Rangkuti, Sofia; Oktarini, Evi Rosana; Sarwendah, Pininto (Bina Nusantara University, 2015)
The study aimed to reveal the social phenomenon in a literary work, especially pedophilia. The research used qualitative approach by applying library research using psychological theory introduced by Sigmund Freud. The data source was Lolita, an English novel, written by Vladimir Nabokov. The analysis is divided into three parts; they are the identification of main character, characterization, and pedophilia. The findings were as follows. First, the main character was Humbert as his high intensity in all the events that build the whole story. Second, the characterization described that the main character was obsessive, possessive, and immoral. Third, the role of literary work revealed pedophilia phenomenon. Finally, it can be concluded that the literary work has played a very important role in revealing the social phenomenon.